2016
DOI: 10.1002/brb3.485
|View full text |Cite
|
Sign up to set email alerts
|

Autonomic and peripheral nervous system function in acute tick‐borne encephalitis

Abstract: ObjectivesTick‐borne encephalitis (TBE) is an emerging flaviviral zoonosis in Central and Eastern Europe. TBE can present as meningitis, meningoencephalitis, or meningoencephalomyelitis. Dysfunction of the autonomic (ANS) and peripheral motoric and sensory nervous system (PNS) might contribute to acute and long‐term complications. We aimed to examine, whether the ANS and PNS are affected in acute TBE.MethodsFourteen patients with acute TBE, 17 with diabetic polyneuropathy (d‐PNP), and 30 healthy controls (HC) … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 11 publications
(6 citation statements)
references
References 23 publications
(57 reference statements)
0
6
0
Order By: Relevance
“…Interestingly, one of the most common clinical manifestations of POWV encephalitis is muscle fatigue. Encephalitis is often associated with increased demyelination [ 57 ] of peripheral nerves [ 58 ] that in turn causes impairment of ion conduction through sensory neurons [ 59 ] resulting in abnormalities in neuromuscular function [ 60 ].…”
Section: Introductionmentioning
confidence: 99%
“…Interestingly, one of the most common clinical manifestations of POWV encephalitis is muscle fatigue. Encephalitis is often associated with increased demyelination [ 57 ] of peripheral nerves [ 58 ] that in turn causes impairment of ion conduction through sensory neurons [ 59 ] resulting in abnormalities in neuromuscular function [ 60 ].…”
Section: Introductionmentioning
confidence: 99%
“…Pathological studies from human post mortem CNS tissue revealed that TBEV selectively affects neurons in the brainstem, cerebellum, basal ganglia, and spinal cord. TBEV antigens were found in >50% of fatal cases in the medullar tegmentum and the pons, including its raphe nuclei and the locus coerulus, which are parts of the central ANS [ 23 ].…”
Section: Discussionmentioning
confidence: 99%
“…The myelitic form is rare (4%-15%), usually being associated with meningoencephalitis, and manifests with flaccid paralysis when motoneurons, radices or peripheral nerves are involved (poliomyelitic or polyradiculoneuritic forms, commonly seen in upper limbs and neck), or rarely with spastic pareses [5,30,[118][119][120][121][122][123]. Occasionally, autonomic disorders have been described in patients with TBE [124,125]. In endemic areas, concomitant TBE and Lyme neuroborreliosis may occur with more severe clinical course [126][127][128].…”
Section: Clinical Characteristicsmentioning
confidence: 99%